Evaluation of calibration methods of Exradin W2 plastic scintillation detector for CyberKnife small-field dosimetry. (August 2022) - Okamura, Keita; Akino, Yuichi; Inoue, Shinichi; Isohashi, Fumiaki; Seo, Yuji; Tamari, Keisuke; Hirata, Takero; Hayashi, Kazuhiko; Fumimoto, Yasutoshi; Ogawa, Kazuhiko
Abstract: Purpose: Plastic scintillation detectors (PSD) require corrections of Cerenkov light for accurate radiation dosimetry. The vendor-recommended calibration method of the Exradin W1 requires irradiation with a 40 × 40 cm 2 field size, although the CyberKnife robotic radiosurgery system cannot generate such large field. Recently, an Exradin W2 PSD, succeeding Exradin W1, was characterized. The W2 PSD can be calibrated in water with small curvature using a new plastic holder, which has a short pole on the bottom to mount it on the arm of the water phantom. The purpose of this study was to evaluate the calibration method of Exradin W2 using the new plastic holder for calibration with small fields and compare the impact of the calibration methods on the beam data. Methods: An Exradin W2-1x1 detector with active volume length 1 mm and diameter 1 mm was used. The Cerenkov light ratio (CLR) values were determined by two calibration methods: measurements in a 30 × 30 cm 2 solid water and in water using a small plastic holder. Percent-depth-dose (PDD), beam profiles, and detector output factor (OFdet ) of TrueBeam 6 MV photon beams with flattening filter (WFF) and flattening filter-free (FFF) beams were measured to compare these two calibration methods. For the CyberKnife photon beams, PDD, beam profiles, and OFdet were measured with the calibration in water, and the data were compared with those measured using a Diode SRS (PTW model 60018) and microDiamond (PTW model 60019). Results: The difference of the CLR between two calibration methods were within 3%. The effect of the calibration methods on the PDD, beam profiles, and OFdet of the TrueBeam were within 0.06%, 0.07%, and 0.8%, respectively. For the CyberKnife beams, the maximum difference of PDD in the dose fall-off region, full-width half-maximum (FWHM) of beam profiles, and penumbra among the three detectors were 1.3%, 0.25 mm, and 0.35 mm, respectively. The relative difference of the W2-measured OFdet from the microDiamond-measured field output factor were within 1.7%. Conclusions: The calibration in water with a small-field size provided equivalent data compared to those obtained with a conventional calibration method. The Exradin W2 provided appropriate data for CyberKnife small-field dosimetry. Highlights: A new plastic scintillation detector, Exradin W2-1x1, was evaluated for CyberKnife. Calibration in water using a new holder was compared with the conventional method. The effects of two calibration methods on the beam data were within 1%. W2-1x1 provided appropriate data of CyberKnife small field dosimetry.